Improving the surface hardness number of subsoil plow chisel using water-jet preening - Sujita, S. (Dinamika Teknik Mesin, 2019)
This study discusses the effects of pressure in waterjet peening (WJP)  of subsoil plow chise. It was made from austenitic stainless steel 301 JIS standard S30100. Analysis of surface integrity and change of surface hardness number is used to evaluate the performance of various parameters in the WJP process. The article summarizes information about austenitic stainless steel physically-mechanical of subsoil plow chisel that is most useful for soil tillage. The subsoil chisel was given surface treatment WJP process with a variation of pressure and time. The physical properties of subsoil plow chisel from various pressure and time of  WJP are analyzed. The findings of this study indicated that surface treatment with waterjet peening could  increase the surface hardness number and the hardening  layer fromaustenitic  stainless steel 301 (material of subsoil plow chisel).Treats the surface with WJP pressure 250 MPa  and time 3 hours  results in a higher increase in surface hardness number  up to 41% and 151% greater than the raw material respectively. Also, a deeper hardening layer to depth 250 and 500 μm each produced. Next, the cross-sectional micro structure shows the density is higher than the slip band in the defective grain of specimens that have undergone the WJP process at the time and higher pressure. However, the number of slip bands in grain defects decreases with     the pressure drop.